Women’s empowerment and child nutrition in a context of shifting livelihoods in Eastern Oromia, Ethiopia - Mechlowitz, Karah; Singh, Nitya; Li, Xiaolong; Chen, Dehao; Yang, Yang; Rabil, Anna; Cheraso, Adriana Joy; Ahmed, Ibsa Abdusemed; Amin, Jafer Kedir; Gebreyes, Wondwossen A.; Hassen, Jemal Y.; Ibrahim, Abdulmuen Mohammed; et al. (Frontiers in Nutrition, 2023)
Agriculture, and particularly livestock and animal source foods, has been closely linked to improvements in human nutrition. Production, income, and women’s empowerment improve household food security and child nutritional outcomes in interacting ways. Khat production in Eastern Ethiopia is changing the economic and livelihood landscape for communities that have traditionally relied upon small-scale mixed agriculture and livestock production. How this shifting livelihood landscape and the empowerment of women in these communities are affecting nutritional outcomes has not been investigated. Using cross-sectional data collected during formative research for the Campylobacter Genomics and Environmental Enteric Dysfunction (CAGED) project, we developed models to examine the roles of livelihood activities, including livestock production, staple crop production, and khat production, and women’s empowerment in child nutrition outcomes. Survey participants were randomly selected mothers of children aged 10-15 months from Haramaya district, Eastern Hararghe, Oromia, Ethiopia. Nested logistic regression models were performed for each nutrition outcome: children’s animal source food consumption, children’s dietary diversity, and child stunting, wasting, and underweight. Explanatory variables included those for livelihood (tropical livestock unit, crop production, and khat production ladder) and women’s empowerment (as indicated by domains of the Women’s Empowerment in Agriculture Index), and covariates including child sex, mother’s age, mother’s education, assets, income, and kebele. Results indicated that khat production and tropical livestock units were not significantly associated with any of the child nutrition outcomes. However, results did indicate that the odds of reporting child animal source food consumption in households where the mother was empowered in the leadership domain was 3.33 times that in households where the mother wasn’t (p < 0.05). In addition, the odds of having a stunted child in households where the mother was empowered in the time domain was 2.68 times that in households where the mother wasn’t (p < 0.05). The results from this study both support and complicate the existing literature on the associations between women’s empowerment in agriculture and child nutrition outcomes, underscoring the important role that livelihood, contextual factors, and location may have on the complex relationship between empowerment domains and nutritional outcomes.